Case of Cocaine Induced Coronary and Carotid Artery Dissection - Tara Gill MS4; Mariaelana Brenner MS4; Janine Beatrice Borja MD-PGY3; Sarah Linder FNP-BC; Saagar Pamulapati MD-PGY1; Prasad Kilaru MD; Vibhav Bansal MD/JD; Roy El Koussa MD PGY1 (SAGE Publishing, 2022)
Cocaine use has been individually linked to both carotid and coronary artery dissections. However, their simultaneous occurrence has not been previously reported. A 30-year-old man who suffered an acute ischemic stroke and myocardial infarction secondary to acute carotid and coronary artery dissections, respectively, 16 hours after snorting cocaine. To our knowledge, this is the first reported case describing the simultaneous occurrence of carotid and coronary artery dissections resulting from cocaine use.